Dignity – often overlooked value in medicine - Čebašek Travnik, Zdenka (Anali PAZU, 2022)
The assumption that every physician knows the true meaning of the word dignity has no solid foundation. The question of definition of dignity is still not resolved, for the majority of respondents is easier to describe its opposite (trample, insult, deny human dignity). Literature search for the Slovenian scientific publications concerning dignity in medicine shows that several texts are written by nurses, also these did not present unified view of it. The impact of the knowledge and understanding of the dignity to the attitude of a doctor or healthcare professional to the patient will be presented with the help of some relevant authors and their publications.
Keywords: dignity; medical deontology; the Constitution of the Republic of Slovenia; the United Nations Convention against Torture and Other Cruel; Inhuman or Degrading Treatment or Punishment; palliative care; professionalism